ASSESSMENT OF BUSINESS PROCESS MANAGEMENT FOR MSMEs IN EAST JAVA - Umi Chotijah (Faculty of Computer Science Universitas Indonesia, 2019)
The role of micro, small and medium enterprises (MSME) for the economy of many countries, especially Indonesia are very important. The garment industry is one of the developing industries in Indonesia. Enterprises need to understanding, documenting, modelling, analyzing, simulating, implementing to increasing the value and achieving business operational efficiency and survive business competition. Therefore, it is necessary to know assess the maturity level of business process management in MSMEs. The purpose of this study is to assess the maturity level of business process management from MSMEs. First, the relevant literature is reviewed to gain insight into the practice of business process management in general, the context of MSME in Indonesia and previous studies related to business process management in the context of MSMEs. This research was conducted in East Java and data collection was done by distributing questionnaires to MSME owners. This study shows that a lack of knowledge resources about BPM is the main factor causes the MSMEs have low business process maturity level.